(3GdeVGQHI aj GdHhQUI (B:s (3GdYdGeGJ GdJLGQjI (B- (3GdJMdHd Gdafj (B- (3GdeQGgfI Ydi GdbQhV GdeGdjI (B/s - (3CdcSfOQ, OjbjOShfs ((3GdbGgQI(B: s (3OGQ GdaGQhb ddfTQ h GdJhRjY(B, s, 2006)
(3HYV GdMbGFb Yf GdeVGQHI aj GdHhQUI h cja JNJGQ GdSeSGQ GdefGSH h cja JUHM eJYGeO LjO aj GdHhQUI? h afhf GOGQI GdGehGd h cjajI GdGSJaGOI Yf GdMSGHGJ GdeGdjI h GdeHGOF GdGSGSjI ddJMdjd Gdafj h cjajI GNJjGQ GdJNWjWGJ GdHjGfjI h cPdc GdeRjO ef GSQGQ GdJMdjd Gdafj h GdeRjO ef CTcGd GdJNWjWGJ GdHjGfjI h cja JSJNOe GdeDTQGJ GdafjI? h cjajI GdGSJaGOI ef YfUQ GdeYdheGJ h ehGba GdJYGed GdNGUI h cjajI GSJNOGe YbhO GdaQb h cPdc JYGedGJ GdeQGgfI Ydi GdaQhb GdeGdjI GVGaI Gdi JYGedGJ TgGOGJ GdCSge GdeZWGI h cjajI GdGSJaGOI ef GdNjGQGJ GdeJOGhdI h GdJYGed HfLGM aj GdYbhO GdBLdI GdeJOGhdI h CQbGe ajfHGJTI h ehLGJ GdjhJ h CNjQG hjdjGe LGf h CSGdjH GdJYGed aj GdShb(B.s
Keywords: (3GOGQI GdGehGds; (3GdHhQUIs; (3GdeVGQHIs